Comparisons of cardiorespiratory and thermoregulatory responses to table tennis and cycling at similar perceived levels of effort - Ishiguro, A.; Amano, T. (Science & Sports, 2022)
Purpose Table tennis is a popular physical activity offering several health benefits. However, the physiological responses to table tennis, relative to other exercise types, have not been fully investigated. A comparison between different exercise types, based on ratings of perceived exertion (RPE), would offer a better physiological characterization of table tennis. We therefore investigated cardiorespiratory and thermoregulatory responses to table tennis relative to cycling at a similar RPE. Methods Eight healthy table tennis players performed 2 sets of 5 minutes simulated table tennis exercise separated by a 5 minutes break by returning a ball ejected from a machine at light (30 balls/min) and moderate (45 balls/min) intensities, respectively. RPE (range, 6-20) was assessed at the end of exercise. On the second visit, they cycled for 5 minutes to meet similar RPE reported during table tennis trial. Physiological responses were assessed during table tennis and cycling trials. Results There was no significant reported difference in RPE between the two exercise types at light (12.9 ± 2.0 and 11.5 ± 1.9 for table tennis and cycling, respectively) and moderate (14.5 ± 0.9 and 14.0 ± 1.4, respectively) intensities, respectively (exercise type effect and interaction, all P = 0.134). Heart rate and oxygen consumption were greater in table tennis than in cycling at both light and moderate intensities (all P = 0.047). No difference in core body temperature was recorded between the exercise types (P = 0.227), but skin temperature was lower in table tennis than in cycling in both intensities (both P = 0.034). Chest sweat rate was slightly greater in table tennis than in cycling at moderate intensity (P = 0.060). Conclusion These results suggest that the cardiopulmonary and thermoregulatory responses of table tennis were greater than those of cycling even at similar RPE.